2016
DOI: 10.1007/s40778-016-0051-7
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Modifications upon Senescence of Mesenchymal Stem Cells

Abstract: Cellular senescence is a continuous and highly organized process that alters the intricate genomic network in order to maintain cellular homeostasis. It occurs in all primary cell cultures-including mesenchymal stem cells (MSCs), which are concurrently tested for a wide variety of clinical applications. Differentiation potential as well as paracrine secretion of MSCs is severely affected by cellular senescence. There is a growing perception that nuclear reorganization and epigenetic modifications contribute to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Frazen et al . recently showed that epigenetic modifications are associated with senescence in hMSCs 72 . Our study has further demonstrated that age related loss of differentiation potential can be rescued through modulating epigenetic modifications by innovatively employing small molecules.…”
Section: Discussionmentioning
confidence: 98%
“…Frazen et al . recently showed that epigenetic modifications are associated with senescence in hMSCs 72 . Our study has further demonstrated that age related loss of differentiation potential can be rescued through modulating epigenetic modifications by innovatively employing small molecules.…”
Section: Discussionmentioning
confidence: 98%
“…Here, we show that Rank-induced senescence is essential for Rank-driven stemness: upon elimination of senescent cells located in the luminal compartment, the enhanced stemness phenotype is lost. TLX and EZH2 targets are enriched in luminal Rank +/tg MECs, suggesting that the stemness/senescence phenotypes may be controlled by epigenetic mechanisms ( Franzen et al., 2016 ; Lee and Schmitt, 2019 ; Orioli and Dellambra, 2018 ; Yang and Sen, 2018 ). Of note, multiple genes were differentially expressed in Rank +/tg basal cells, including downregulation of the p53 target p21 , indicative of a luminal/basal crosstalk.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to aging, CFU-F frequency within the bone marrow generally declines with age, and the capacity of the remaining MSCs to withstand oxidative stress appears to also decline along with their function and therapeutic efficacy [ 129 131 ]. Such functional changes may be the result of progressively shortening telomeres, accumulated molecular damage, and stochastic genetic and epigenetic changes over time [ 132 136 ]. Such age-associated epigenetic dysregulation may also contribute to alterations in the differentiation potential and heterogeneity of MSCs [ 137 , 138 ].…”
Section: Ipsc Sources and Epigenetic Reprogramming Of Mscsmentioning
confidence: 99%